(untitled) (Journal of the College of Basic Education, 2025)
The current research aims to identify the effect of the three cups strategies and the spiral of discussion on the achievement of geography among fourth grade literary students and the development of their critical thinking. To achieve the research objectives, the researcher adopted the experimental method, where the study sample consisted of (104) students distributed into three groups.There were (35) students in the first experimental group, which studied geography using the Three Cups strategy, (35) students in the second experimental group, which studied geography using the discussion spiral strategy, and (34) students in the control group, which studied the same subject in the traditional way. . The researcher conductedEquivalence between the research groups in the variables (prior knowledge, intelligence test, chronological age, critical thinking test). The researcher prepared a post-achievement test consisting of (40) multiple-choice and essay-type items, and confirmed its validity, stability, and psychometric properties. The thinking scale was adopted. The critic prepared by (Al-Dulaimi: 2007)The researcher used the statistical program (SPSS) to analyze the data statistically. The study found that the students of the two experimental groups outperformed the students of the control group in the achievement test and the critical thinking test.